2022
DOI: 10.3390/ijms232113435
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Response in Adipose Tissue-Derived Mesenchymal Stem/Stromal Cells

Abstract: Reactive oxygen species (ROS) can irreversibly damage biological molecules, a process known as oxidative stress. Elevated ROS levels are associated with immune cell activation. Sustained immune system activation can affect many different cells in the environment. One cell type that has been detected in almost all tissues of the body is mesenchymal stem/stromal cells (MSC). MSC possess proliferation and differentiation potential, thus facilitating regeneration processes. However, the regenerative capacity of MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…To further study the reason that composite particles could prove the recruitment of BMSC through cascade reaction, the secretion of chemokines SDF-1 as well as HGF was detected by Elisa kit under P-CM condition. HGF secretion promotes MSC migration via the HGF/c-Met signaling pathway. , In addition, SDF-1 is a stem cell chemokine receptor that promotes stem cell migration via the SDF-1/CXCR4 axis. Relative expression of HGF and SDF-1 from BMSCs cocultured with particles on 5 days are shown in Figure g,h. Compared with CPP, ECPP particles significantly enhanced the secretion of both HGF and SDF-1 from BMSCs due to the release of Eu ions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further study the reason that composite particles could prove the recruitment of BMSC through cascade reaction, the secretion of chemokines SDF-1 as well as HGF was detected by Elisa kit under P-CM condition. HGF secretion promotes MSC migration via the HGF/c-Met signaling pathway. , In addition, SDF-1 is a stem cell chemokine receptor that promotes stem cell migration via the SDF-1/CXCR4 axis. Relative expression of HGF and SDF-1 from BMSCs cocultured with particles on 5 days are shown in Figure g,h. Compared with CPP, ECPP particles significantly enhanced the secretion of both HGF and SDF-1 from BMSCs due to the release of Eu ions.…”
Section: Resultsmentioning
confidence: 99%
“…HGF secretion promotes MSC migration via the HGF/c-Met signaling pathway. 49,50 In addition, SDF-1 is a stem cell chemokine receptor that promotes stem cell migration via the SDF-1/CXCR4 axis. 51−53 Relative expression of HGF and SDF-1 from BMSCs cocultured with particles on 5 days are shown in Figure 6g,h.…”
Section: Effect Of Particles On Stem Cell Recruitmentmentioning
confidence: 99%
“…This increased migratory activity is accompanied by a CAP-induced increase in intracellular Ca 2+ levels. Studies have shown that increased intracellular Ca 2+ levels can be associated with increased adMSC migration [69]. So far, however, there are only a few studies to date that have investigated the influence of CAP on cell migration, and these results cannot be described as conclusive overall: Direct treatment with CAP to murine fibroblast or a human glioblastoma cell line reduced the migration of the respective cells [70,71].…”
Section: Cell Signaling Antioxidative Response and Cellular Functions...mentioning
confidence: 99%
“…In summary, the treatment of adMSC cultures with a CAP-activated medium did not cause cytotoxic effects when the treatment was short-term and non-repetitive. The known antioxidant capacity of MSCs [23,69] is probably responsible for the low intracellular ROS levels after treatment with a CAP-activated medium. In addition, short-term treatment with a CAP-activated medium resulted in increased migration and increased intracellular Ca 2+ levels.…”
Section: Cell Signaling Antioxidative Response and Cellular Functions...mentioning
confidence: 99%
“…However, the regenerative capacity of MSC might be impaired by oxidative stress: short- and long-term oxidative stress can be mimicked by exposure to H 2 O 2 with or without glucose oxidase (GOx), respectively. It emerged that prolonged GOx-induced exposure to H 2 O 2 allows for better cellular adaptation; however, the mechanism to explain the difference between short- and long-term adaptation is not clear [ 8 ]. Tereza Souralova et al describe current good manufacturing practice (cGMP) that has to be implemented in the transport of embryos, the derivation of the inner cell mass to xeno-free, feeder-free and defined hESC culture, and cell freezing.…”
mentioning
confidence: 99%